Targeted three-dimensional immunohistochemistry reveals localization of presynaptic proteins Bassoon and Piccolo in the rat calyx of Held before and after the onset of hearing - Dondzillo, Anna; Sätzler, Kurt; Horstmann, Heinz; Altrock, Wilko D.; Gundelfinger, Eckart D.; Kuner, Thomas (The journal of comparative neurology, 2010)
Bassoon and Piccolo contribute to the cytomatrix of active zones (AZ), the sites of neurotransmitter release in nerve terminals. Here, we examined the 3D localization of Bassoon and Piccolo in the rat calyx of Held between postnatal days 9 and 21, the period of hearing onset characterized by pronounced structural and functional changes. Bassoon and Piccolo were identified by immunohistochemistry (IHC) on slices of the brainstem harboring calyces labeled with membrane-anchored green fluorescent protein (mGFP). By using confocal microscopy and 3D reconstructions, we examined the distribution of Bassoon and Piccolo in calyces delineated by mGFP. This allowed us to discriminate calyceal IHC signals from noncalyceal signals located in the spaces between the calyceal stalks, which could mimic a calyx-like distribution. We found that both proteins were arranged in clusters resembling the size of AZs. These clusters were located along the presynaptic membrane facing the principal cell, close to or overlapping with synaptic vesicle (SV) clusters. Only about 60% of Bassoon and Piccolo clusters overlapped, whereas the remaining clusters contained predominantly Bassoon or Piccolo, suggesting differential targeting of these proteins within a single nerve terminal and potentially heterogeneous AZs functional properties. The total number of Bassoon and Piccolo clusters, which may approximate the number of AZs, was 405 ± 35 at P9 and 601 ± 45 at P21 (mean ± SEM, n = 12). Normalized to calyx volume at P9 and P21, the density of clusters was similar, suggesting that the absolute number of clusters, not density, may contribute to the functional maturation associated with hearing onset.